Is There a Downside of Job Accommodations? An Employee Perspective on Individual Change Processes - Kensbock, Julia M.; Boehm, Stephan A.; Bourovoi, Kirill (Frontiers in Psychology, 2017)
By modifying the work environments, work routines, and work tasks of employees with health restrictions, organizations can effectively help them continue to perform their jobs successfully. As such, job accommodations are an effective tool to secure the continued employment of aging workers who develop disabilities across their life span. However, while accommodations tackle health-related performance problems, they might create new challenges on the part of the affected employee. Building on the organizational change and accommodations literatures, we propose a theoretical framework of negative experiences during accommodation processes and apply it to qualitative data from group interviews with 73 manufacturing workers at a German industrial company who were part of the company’s job accommodation program. Although problems associated with health-related impairments were mostly solved by accommodation, affected employees with disabilities reported about interpersonal problems and conflicts similar to those that typically occur during organizational change. Lack of social support as well as poor communication and information were raised as criticisms. Furthermore, our findings indicate that discrimination, bullying, and maltreatment appear to be common during accommodation processes. To make accommodation processes more successful, we derive recommendations from the organizational change literature and apply it to the accommodation context. We also emphasize unique characteristics of the accommodation setting and translate these into practical implications.